2014
DOI: 10.1097/scs.0000000000000672
|View full text |Cite
|
Sign up to set email alerts
|

Transport Distraction Osteogenesis With Recombinant Human Bone Morphogenic Protein-2 for Large Calvarial Defect Reconstruction

Abstract: TDO with an internal distraction device delivering rhBMP-2 can enhance bone regeneration of large calvarial defects in a dog model. These results suggest the potential for human clinical testing of TDO combined with rhBMP-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…There is growing evidence of the reliability of applying bone transport DO experimentally in the management of calvarial defects in animals. Song et al 17 demonstrated the effectiveness and the promising results of bone regeneration (clinically, histologically, and using 3D CT) using transport DO combined with recombinant human bone morphogenic protein-2 in dog models with large calvarial defects.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence of the reliability of applying bone transport DO experimentally in the management of calvarial defects in animals. Song et al 17 demonstrated the effectiveness and the promising results of bone regeneration (clinically, histologically, and using 3D CT) using transport DO combined with recombinant human bone morphogenic protein-2 in dog models with large calvarial defects.…”
Section: Discussionmentioning
confidence: 99%